2022
DOI: 10.21203/rs.3.rs-1200288/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of multicellular longitudinally dividing oral cavity symbionts (Neisseriaceae)

Abstract: In spite of the staggering number of bacteria that live associated with animals, the growth mode of only a few symbionts has been studied so far. Here, we focused on multicellular longitudinally dividing (MuLDi) Neisseriaceae occurring in the oral cavity of mammals and belonging to the genera Alysiella, Simonsiella and Conchiformibius. Firstly, by applying comparative genomics coupled with ultrastructural analysis, we inferred that longitudinal division evolved from a rod-shaped ancestor of the Neisseriaceae f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
(111 reference statements)
1
2
0
Order By: Relevance
“…In this report, we show that similar to previous studies conducted in other organisms, MraZ is a transcriptional regulator in B. subtilis (11-13, 16). Specifically, it is important in repressing the expression of two essential cell division genes pbpB and ftsL , in addition to the non-essential mraW gene described above, which does not appear to have a direct role in cell division (10) ( Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this report, we show that similar to previous studies conducted in other organisms, MraZ is a transcriptional regulator in B. subtilis (11-13, 16). Specifically, it is important in repressing the expression of two essential cell division genes pbpB and ftsL , in addition to the non-essential mraW gene described above, which does not appear to have a direct role in cell division (10) ( Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Work in Burkholderia cenocepacia has shown that P mra is the sole transcription start site of the dcw cluster and MraZ can bind to the promoter sequence and presumably act as a transcriptional regulator (15). Recent investigation of Neisseriaceae family organisms revealed that deletion of mraZ among others factors may have allowed for the evolution of alternate growth modes (16). A recent report in Staphylococcus aureus proposes a role for MraZ in virulence regulation (17).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, as shown in Fig. 2, our approach can be used to generate markerless deletions and insertions (as demonstrated here), but can also be used to generate markerless complementation strains of a previous deletion by inserting the gene in another locus (Nyongesa et al 2022). Similar approaches for markerless modifications of bacteria employ the use of two-gene cassettes comprising a resistance gene for selection and rpsL wt for counterselection (Johnston and Cannon 1999;Sander et al 2001;Sung et al 2001;Bird et al 2011;Kaczmarczyk et al 2012).…”
Section: Discussionmentioning
confidence: 99%